Research of concentration of operations is in modern furniture production - Gayda, Serhiy (Forestry, Forest, Paper and Woodworking Industry, 2007)
Explored indexes of flexibility and mobility of equipment in a furniture production. Annual balance of work of different type of equipment is expected. Artificially-calculation time of treatment of details is analysed on a processing center. Comparative efficiency of capability of the flexible systems of productions is resulted.